Impact of wearing external breast prosthesis on body posture of patients after unilateral mastectomy: a randomized controlled trial - Xie, HongMei; Lan, XiaoQian; Wang, YueHua; Wang, QiuZhou; Ye, Zi; Chen, Hong; Fu, Lan (Frontiers in Oncology, 2025)
IntroductionUnilateral mastectomy induces postural alterations; however, the resolution of this issue in clinical settings remains unknown. This study aimed to explore the effects of wearing external breast prosthesis on the posture of patients after unilateral mastectomy.MethodsA total of 240 patients who underwent unilateral mastectomy for breast cancer in our hospital’s breast surgery department from September 2020 to March 2021 were selected, and they were registered and randomized in a 1:1 ratio to receive one of two treatments: (1) the intervention group wearing a external breast prosthesis (similar in weight to the breast) and (2) the control group wearing a cotton breast prosthesis (almost no weight). The generalized estimating equation method was used to analyze the impact of wearing external breast prosthesis on the patients’ body posture 3 and 6 months after the intervention.ResultsStatistically significant differences were observed between the two groups regarding forward head posture, shoulder asymmetry, scapular tilt, and neck tilt (P < 0.05). However, the two groups had no significant differences in scapular adduction/abduction, pelvic tilt, and trunk inclination (P > 0.05). Over time, all degrees of deviation in postural abnormalities exhibited an upward trend, with postural abnormalities becoming increasingly serious.DiscussionExternal breast prosthesis can improve postural abnormalities in patients with forward head posture, shoulder asymmetry, and scapular and neck tilts. However, there was no significant improvement in the short-term body posture of the patients concerning scapular adduction/abduction, pelvic tilt, or trunk inclination, indicating that further research is required to understand the effects of wearing external breast prosthesis on patients’ body posture.China clinical trial registryhttps://www.chictr.org.cn/showproj.html?proj=56939, identifier ChiCTR2000040897.